2009
DOI: 10.1007/s11418-009-0336-6
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive, antipyretic, and anti-inflammatory activities of Putranjiva roxburghii Wall. leaf extract in experimental animals

Abstract: The effects of the ether extract from the leaves of Putranjiva roxburghii (P. roxburghii) Wall. were assessed on nociceptive responses in mice by using writhing, hot plate, and formalin tests and the antipyretic activity was determined in yeast-induced fever in rats. Anti-inflammatory activities were also investigated using carrageenin-induced paw edema in rats and croton oil-induced ear and anus edemas. The ether extract (100, 200, and 400 mg/kg, p.o.) of P. roxburghii dose-dependently produced analgesic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 20 publications
0
50
0
4
Order By: Relevance
“…In comparison, the ether extract was slightly less potent than Indomethacin on nociceptive response in rats 39 as described by Wantana Reanmongkol et al 2009. These results indicated that the P.roxburghii ethanolic extract may possess significant antinociceptive activity.…”
Section: Multi-model Analgesic Activity Of Proxburghii Stem-leaves Ementioning
confidence: 56%
“…In comparison, the ether extract was slightly less potent than Indomethacin on nociceptive response in rats 39 as described by Wantana Reanmongkol et al 2009. These results indicated that the P.roxburghii ethanolic extract may possess significant antinociceptive activity.…”
Section: Multi-model Analgesic Activity Of Proxburghii Stem-leaves Ementioning
confidence: 56%
“…Fever has been recognized as a major sign of diseased condition right from the very beginning of human civilization. The febrile response is coordinated by the central nervous system through endocrine, neurological, immunological and behavioral mechanisms [27]. The initiation, manifestations and regulation of the febrile response are dependent on the pyrogenic and anti-pyrogenic properties of various exogenous and endogenous substances.…”
Section: Antipyretic Studymentioning
confidence: 99%
“…Traditionally, its rhizomes have been used medically to treat colic, obesity and rheumatism, asthma and coughs, scurvy and mental derangement 1 . This plant has been reported to have various pharmacological activities like antioxidant 2 , anti-inflammatory 3 , inhibitory of HIV-1 4 , anti-cancer 5 , and antifungal 6 . The C. aeruginosa rhizome has three levels of different parts, namely the primary rhizome (PR), the secondary rhizome (SR) and tertiary rhizome (TR).…”
Section: Introductionmentioning
confidence: 99%